HUBUNGAN ANTARA DURASI BERKENDARA TERHADAP RISIKO NYERI PUNGGUNG BAWAH PADA KURIR EKSPEDISI - Erina Pramesti (2023)
Background: Low Back Pain is the most common health case, ranging from 50-80% among adults based on working age. Individuals are likely to have experienced Low Back Pain at some point with a recurrence rate of up to 85%. Motorcycles are the main means of transportation for almost to everyone. One of the factors that can influence the onset of complaints of low back pain is the long duration of driving. Research Purposes: To be able to determine the relationship between driving duration and complaints of low back pain in expedition couriers. Methods: This study uses a correlational quantitative research design with a cross-sectional approach. With a sample of 67 expedition couriers with an error rate of 5%. This research was conducted online through a Google form questionnaire. Results Researches: The results shown that obtained for the highest value of driving duration were in the category of more than four hours with a percentage of 95.5% and the value in the no risk category of low back pain was the highest with a percentage of 59.7%. Bivariate analysis is using the chi square test to determine the relationship between the driving duration and the risk of low back pain obtained the result of P 0.394 < 0.05 with a weak relationship. The conclusion of this studies resulted is there was no relationship between the driving duration and the risk of low back pain in expedition couriers.